2001
DOI: 10.2214/ajr.176.6.1761399
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution CT Analysis of Small Peripheral Lung Adenocarcinomas Revealed on Screening Helical CT

Abstract: Small peripheral lung adenocarcinomas shown on CT exhibit four high-resolution CT patterns that corresponded to the histopathologic findings of different tumor growth patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(71 citation statements)
references
References 27 publications
2
69
0
Order By: Relevance
“…Its shape is proportional to the growth velocity of each part of the peripheral lung cancer and is blocked by the larger pulmonary vessels and bronchi [7,8]. The form of cavitary inner wall depends on whether the tissue necrosis of the tumour is even or whether there is a wall nodule.…”
Section: Discussionmentioning
confidence: 99%
“…Its shape is proportional to the growth velocity of each part of the peripheral lung cancer and is blocked by the larger pulmonary vessels and bronchi [7,8]. The form of cavitary inner wall depends on whether the tissue necrosis of the tumour is even or whether there is a wall nodule.…”
Section: Discussionmentioning
confidence: 99%
“…Part solid or solid presentations have been correlated to alveolar collapse (12) or rare mucinous types. A recent case report showed that gravity may increase artificially the density of pure GGO nodules located in the posterior lung Mucinous BAC Part solid GGO / solid Consolidation malignant nonsolid nodules were described in a small series (20): increase in size of the nonsolid area (n = 5); reduction in size of the nonsolid area coupled with appearance of a solid component (n = 2); stable dimension of the nodule but progression from non-solid to a part-solid nodule (n = 1).…”
Section: Ct/histopathological Correlationmentioning
confidence: 99%
“…The tumor is more frequently discovered by radiographic examination. Radiologists very often describe the computed tomography (CT) scan appearance of a pure BAC as that of ground-glass opacity (GGO) 8,9 ; however, there is no consensus among radiologists on a defined radiographic appearance for BAC, mostly because not all pure GGO lesions, when excised, correspond to pure BAC histologically. Studies of radiographic-histologic correlations have showed that pure GGO can have a component of invasive adenocarcinoma admixed with a BAC growth pattern, 10 and invasive adenocarcinomas, such as pure papillary type, can present radiographically as a GGO.…”
Section: Overviewmentioning
confidence: 99%